2012
DOI: 10.1007/s12602-012-9113-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Inocula Conditions for Enhanced Biosurfactant Production by Bacillus subtilis SPB1, in Submerged Culture, Using Box–Behnken Design

Abstract: The inoculum age and density can influence considerably the production yield and cost of the fermentation process. Some literature studies report the use of two-stage inocula to enhance metabolite production. In the present study, optimization studies were done in order to define the best inocula conditions supporting a maximum biosurfactant production by Bacillus subtilis SPB1. Hence, by adjusting the levels of the two-stage inocula strategy, lipopeptide production was effectively enhanced to almost 3.4 g/l a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…The higher number of cells may increase the competition for the nutrients for cell maintenance rather than the production of biosurfactant (Ghribi and Ellouze-Chaabouni, 2011; Onwosi and Odibo, 2013; Nalini and Parthasarathi, 2014). Inoculum size has demonstrated high influence on biosurfactant production in previous studies and can have a definite effect on economics of a microbial process (Mnif et al, 2013; Onwosi and Odibo, 2013). The CCRD conducted by Lima and Souza (2014) showed that the inoculum concentration was the factor that had the greatest effect on biosurfactant production by Bacillus subtilis PC, providing the best surface tension values of the 32 mNm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The higher number of cells may increase the competition for the nutrients for cell maintenance rather than the production of biosurfactant (Ghribi and Ellouze-Chaabouni, 2011; Onwosi and Odibo, 2013; Nalini and Parthasarathi, 2014). Inoculum size has demonstrated high influence on biosurfactant production in previous studies and can have a definite effect on economics of a microbial process (Mnif et al, 2013; Onwosi and Odibo, 2013). The CCRD conducted by Lima and Souza (2014) showed that the inoculum concentration was the factor that had the greatest effect on biosurfactant production by Bacillus subtilis PC, providing the best surface tension values of the 32 mNm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The metabolite accumulation and cell growth were also highly influenced by composition of the medium such as carbon and nitrogen sources, C:N ratio and other factors that affect the growth . It is obvious that the medium components play critical role in improved biosynthesis of the metabolites, thus optimizing cultural conditions could enhance the yield of biosurfactants …”
Section: Resultsmentioning
confidence: 99%
“…Thus, the oil contaminated sites are envisaged as enriched source of biosurfactant‐producing microorganisms . So far, most of research in the field of biosurfactants has been carried out using bacteria and yeasts, however, biosurfactants from different filamentous fungi have also been reported by a few scientists . Unlike other oleaginous microbes, filamentous fungi are considered as dynamic mini‐eukaryotic biofactories for production of many industrially important biotechnological products, including commercial enzymes, organic acids, alkaloids, plant growth regulators, antibiotics, polysaccharides, and pigments .…”
Section: Introductionmentioning
confidence: 99%
“…A B. subtilis strain lipopeptide production was optimized to 3.4 gL −1 using a BBD [39]. Primary inoculum age, secondary seed culture age, and size were the factors evaluated.…”
Section: Box-behnkenmentioning
confidence: 99%
“…A lower initial cell density also increased Bs productivity. This was explained by the fact that in the case of sporulating bacteria like B. subtilis, less and younger biomass would lengthen the exponential phase where the Bs can be produced; since once the stationary phase is reached sporulation processes are induced [39].…”
Section: Box-behnkenmentioning
confidence: 99%